Community projects: An experimental analysis of a fair implementation process - Simona Cicognani; Anna D'Ambrosio; Werner Güth; Sinome Pfuderer; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We define and experimentally test a public provision mechanism that meets three basic ethical requirements and allows community members to influence, via monetary bids, which of several projects is implemented. For each project, participants are assigned personal values, which can be positive or negative. We provide either complete or only private information about others' personal values. This produces two distinct public provision games which are experimentally implemented and analysed for various projects. In spite of the complex experimental task, participants do not rely on truth-telling as an obvious and simple heuristic whose general acceptance would result in fair and efficient outcomes. Rather, they yield to strategic underbidding. Although underbidding is affected by projects' characteristics, the provision mechanism seems quite functional.
Keywords: C91; C72; D63; 330; Public Provision; Procedural Fairness; Experiment; Öffentliches Gut; Spieltheorie; Gerechtigkeit; Gemeinschaft; Projektbewertung; Test